2001
DOI: 10.1254/jjp.87.61
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Activity of Natural Isorhapontigenin

Abstract: ABSTRACT-Isorhapontigenin (ISOR), isolated from Belamcanda chinensis, is a derivative of stilbene. Its chemical structure is very similar to that of resveratrol, with a potent antioxidative effect. In the present study, we investigated the antioxidative activity of ISOR in vitro. Oxidative damage of rat liver microsomes, brain mitochondria and synaptosomes was induced by Fe 2+ -Cys, VitC-ADP-Fe 2+ and H2O2, respectively. The formation of malondialdehyde (MDA), decrease of reduced glutathione (GSH) and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…4). In a study by Wang et al [41], they reported that the inhibition of MDA formation by ISOR is about 100 times more potent than that of the classical anti-oxidant vitamin E at the same concentration. Also, in a recent study, Wang et al [40] found that REV and its analogue ISOR may effectively upregulate the expression of SOD2 and GPX1 in hematopoietic cells following ionizing radiation-induced injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). In a study by Wang et al [41], they reported that the inhibition of MDA formation by ISOR is about 100 times more potent than that of the classical anti-oxidant vitamin E at the same concentration. Also, in a recent study, Wang et al [40] found that REV and its analogue ISOR may effectively upregulate the expression of SOD2 and GPX1 in hematopoietic cells following ionizing radiation-induced injury.…”
Section: Discussionmentioning
confidence: 99%
“…Group I included normal rats that received vehicle (2 ml of physiological saline) by intraperitoneal injection on two consecutive days with an interval of 24 h between applications. Group II included normal rats administered ISOR (10 −6 mol/L, in drinking water) [41] for 30 days. Group III included normal rats administered n-3 PUFA (0.3 g/kg/day by gavage) [8] for 30 days.…”
Section: Experimental Designmentioning
confidence: 99%
“…In response to these, I. obliquus has evolved a complex series of integrated defense systems. In recent years, more than 20 different kinds of bioactive components have been found in I. obliquus mainly including inooidiol the precursor of vitamin D2, betulinic acid, oxygenated triterpenes (Handa et al, 2010), superoxide dismutase (SOD), trametenolic acid, dextran, tannin compounds, steroids, alkaloid, lanosterol (Nakamura et al, 2009), lanoline alkane type three terpenes, lignin, melanin catechol (Zheng et al, 2009), folic acid derivatives, sheath ammonia fat analogs, mannitol, polyphenol, lanosterol (Wang et al, 2001), half the tannin compounds, aromatic substances (Zhao and Piao, 2006;Taji et al, 2008), β-glucan (Rhee et al, 2008), peptides (Hyun et al, 2006), polysaccharides (Cui et al, 2005;Zhang et al, 2007;Nakajima et al, 2007), polyphenols (Cui et al, 2005;Lee et al, 2007), triterpenoids, and steroids (Cui et al, 2005). Some components and their effects on tumor cell can be found in Table 1.…”
Section: Inonotus Obliquus and Bioactive Constituentsmentioning
confidence: 99%
“…The process of ischemiareperfusion increased rat brain MDA levels to 5.5 nmol/mg from 3.5 nmol/mg in controls [18]. Wang et al [19] reported that the MDA concentration in brain cortex mitochondria in rat was 8.38 nmol/mg, which was increased to 24.63 nmol/mg by exposure to Fe 2? -Cys.…”
Section: Introductionmentioning
confidence: 95%